Radiographic, Electrocardiographic and Echocardiographic Evaluation in dogs with ascites - Lalitha B; Shobhamani, B; Sudhakar Goud, K; Malakondaiah, P; Rajesh, K; Vaikunta Rao, V (Indian Journal of Veterinary Medicine, 2025)
The present study was carried out at Veterinary Clinical Complex, College of Veterinary Science, Tirupati from May 2024 to November 2024. Animals presented with the history of abdominal distension, anorexia, respiratory distress and pedal oedema were selected for study. Diagnosis of ascites was done by radiography, ultrasonography and echocardiography. Radiographic findings were characteristic ground glass appearance. Ultrasonographic findings were hepatomegaly, hyperechoic, hypoechoic and mixed echogenicity of liver parenchyma etc. Echocardiographic findings were dilated cardiomyopathy, congestive heart failure, pericardial effusions etc.